Hubungan Caring Perawat Terhadap Loyalitas Pasien di Rumah Sakit - Nur Afifah; Sri Yulia; Muliyadi Muliyadi (Universitas Muhammadiyah Surakarta, 2019)
Patient loyalty can affect hospital development, so it is necessary to control the influencing factors, one of them is by improving the quality of nursing services through a caring approach. The purpose of this study was to identify nurse’s caring at Palembang XX Hospital. Quantitative research methods with a correlative descriptive design and cross sectional approach was used in this research. The sampling technique was accidental sampling with 38 respondents. Data collection tools using questionnaires as many as 25 items caring nurse statements and 18 items of patient loyalty statements. Data analysis used the chi square test. The results of the research are caring nurses good 30 respondents (78.9%), contractual aspects are good 23 respondents (60.5%), ethical aspects are good 28 respondents (73.3%), spiritual aspects are good 24 respondents (63.2%) and good loyalty 24 respondents (63.2%). Research results show that there is a nurse caring relationship with loyalty (p value = 0.034), there is a relationship between contractual aspects and loyalty (p value = 0.006), there is a relationship between ethical aspects and loyalty (p value = 0.021) there is a relationship between spiritual aspects and loyalty ( p value = 0.035). The conclusion and suggestion is that there is a nurse caring relationship with patient loyalty. Efforts need to be made to improve caring nurses by making guidelines on caring nurses